1994
DOI: 10.1111/j.1469-8137.1994.tb03999.x
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and co‐tolerance of the grass Chloris barbata Sw. to mercury, cadmium and zinc

Abstract: summary Races of Chloris barbata Sw. from a mercury‐contaminated site in the vicinity of a chloralkali plant and from a non‐contaminated site were tested for their relative tolerance to mercury, cadmium and zinc. Pre‐rooted tillers of each of the races were grown in calcium nitrate solution, Ca(NO3)2, 4H2O, l gl−1 with or without HgCI2 (0.001, 0.01, 0.05, 0.1 and mgl−1), CdSO4.8H2O (0.05, 1.0, 2.5 and 5 mg l−1 and ZnSO4 7H2O (1, 5, 10, 20 and 40 mg l−1) for a period of 5 d, Metal tolerance was evaluated by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 40 publications
2
24
0
1
Order By: Relevance
“…These data clearly demonstrate the significant difference between Al-tolerant and Al-sensitive barley cultivars. Similar results were described by Patra et al (1994) where stronger activation of acid phosphatase was observed in tolerant grass than in non-tolerant during mercury and cadmium treatment. Phosphatase isoenzyme pattern always contain different numbers of isoenzymes.…”
Section: Resultssupporting
confidence: 78%
“…These data clearly demonstrate the significant difference between Al-tolerant and Al-sensitive barley cultivars. Similar results were described by Patra et al (1994) where stronger activation of acid phosphatase was observed in tolerant grass than in non-tolerant during mercury and cadmium treatment. Phosphatase isoenzyme pattern always contain different numbers of isoenzymes.…”
Section: Resultssupporting
confidence: 78%
“…Protein carbonyls were determined in matrices and membranes of peroxisomes by measuring the complex formed with 2,4-dinitrophenylhydrazine (Levine et al 1991). Total-, protein-, and non-protein-thiols were measured as the complex formed with 5,5'-dithiobis(2-nitrobenzoic) acid (Patra et al 1994).…”
Section: Methodsmentioning
confidence: 99%
“…We earlier reported regarding the evolution of metal-tolerance in the grass Chloris barbata Sw. growing at an abandoned solid-waste dump site near a chloralkali plant at Ganjam, India, which was highly contaminated with toxic levels of mercury (Lenka et al 1992, Patra et aL 1994. In this paper we present the difference in antioxidant and thiol responses of the aforesaid non-tolerant (NT) vis-fi-vis tolerant (T) clones of C. barbata to Cd-stress.…”
Section: Introductionmentioning
confidence: 96%